PENGUASAAN FITUR-FITUR PENTING MICROSOFT WORD UNTUK MENINGKATKAN KETERAMPILAN PENULISAN TUGAS DAN LAPORAN YANG KREATIF DAN PROFESIONAL BAGI SISWA SMP AL – AMANAH - Nurhasanah; An Najmi As Syfa; Anggita Tri Sundari; Muhammad Fadhiil Agam; Muhammad Iqbal Wibowo; Muhammad Qosim Nur Abid; Nouval Ferdiansyah; Rahmat Tamim; Rhevo Aliffiano Marshandy; Yanuar Nurfirgiansyah; Zulfa Bahrul Akmal (Abdi Jurnal Publikasi, 2024)
In the digital era, mastering information technology is essential for students, particularly in utilizing word processing software like Microsoft Word. This community service proposal aims to enhance the writing skills of SMP Al-Amanah students by providing training on important features of Microsoft Word. The training will cover text formatting, table creation, and the use of visual elements to produce organized and professional documents. By addressing the current limitations in students' skills, this program seeks to prepare them for academic and professional challenges ahead. The workshop will involve interactive sessions and practical exercises, ensuring that students can apply their knowledge effectively. The expected outcome is an improvement in the quality of students' assignments and reports, fostering creativity and professionalism in their writing.